Massive Conscious Neighborhood-Based Crow Search Algorithm for the Pseudo-Coloring Problem - Simplicio Viana, Monique; Contreras, Rodrigo Colnago [UNESP]; Pessoa, Paulo Cavalcanti; Bongarti, Marcelo Adriano dos Santos; Zamani, Hoda; Guido, Rodrigo Capobianco [UNESP]; MorandinJunior, Orides (Springer Nature, 2024)
The pseudo-coloring problem (PsCP) is a combinatorial optimization challenge that involves assigning colors to elements in a way that meets specific criteria, often related to minimizing conflicts or maximizing some form of utility. A variety of metaheuristic algorithms have been developed to solve PsCP efficiently. However, these algorithms sometimes struggle with the quality of solutions, impacting their ability to achieve optimal or near-optimal results reliably. To overcome these issues, this study introduces an adapted conscious neighborhood-based crow search algorithm (CCSA) and a massive variant of CCSA specifically tailored for PsCP. The performance of CCSA and MCCSA are evaluated on real and synthetic images and compared with state-of-the-art optimizers. The results showed that the adapted CCSA and MCCSA outperformed offering an effective strategy for image pseudo-colorization.
Keywords: Color Spaces; Crow Search Algorithm; Massive Local Search; Optimization; Pseudo-Coloring Problem